Nanoparticulation of Prodrug into Medicines for Cancer Therapy - Zhang Yuezhou; Cui Huaguang; Zhang Ruiqi; Zhang Hongbo; Huang Wei (WILEY, 2022)
This article provides a broad spectrum about the nanoprodrug fabrication advances co-driven by prodrug and nanotechnology development to potentiate cancer treatment. The nanoprodrug inherits the features of both prodrug concept and nanomedicine know-how, attempts to solve underexploited challenge in cancer treatment cooperatively. Prodrugs can release bioactive drugs on-demand at specific sites to reduce systemic toxicity, this is done by using the special properties of the tumor microenvironment, such as pH value, glutathione concentration, and specific overexpressed enzymes; or by using exogenous stimulation, such as light, heat, and ultrasound. The nanotechnology, manipulating the matter within nanoscale, has high relevance to certain biological conditions, and has been widely utilized in cancer therapy. Together, the marriage of prodrug strategy which shield the side effects of parent drug and nanotechnology with pinpoint delivery capability has conceived highly camouflaged Trojan horse to maneuver cancerous threats.